Ecoacoustics as a novel tool for assessing pond restoration success: Results of a pilot study. Issue 8 (19th May 2021) - Greenhalgh, Jack A.; Stone, Harold J. R.; Fisher, Tom; Sayer, Carl D.
Abstract: Ecoacoustics is increasingly being used to monitor species populations and to estimate biodiversity in marine ecosystems, but the underwater soundscapes of freshwater environments remain largely unexplored in this respect. Few studies exist concerning the acoustic diversity of ponds, but because aquatic plants and many arthropods such as Coleoptera and Hemiptera are known to produce sound, there is potential to use ecoacoustic techniques to monitor changes in biodiversity and conservation value. This pilot study compares the underwater soundscapes of recently restored open‐canopy ponds and unmanaged highly terrestrialized ponds situated in an arable agricultural landscape of North Norfolk, UK, in order to assess the benefits of farmland pond restoration. Daytime sound recordings were made for 10 min in each pond and analysed primarily for arthropod stridulations. In addition, six commonly used acoustic indices were calculated to assess the soundscape biodiversity between the unmanaged and the restored ponds. The stridulations of three diving beetle species (Dytiscidae) were recorded in tank studies to assess the potential for individual species recognition from underwater sound capture. Sound‐type richness and abundance, as estimated by visually and aurally identifying arthropod stridulation from spectrograms, were significantly higher in the restored open‐canopy ponds compared with the unmanaged terrestrialized ponds. In addition, the acoustic indices 'acoustic complexity' and 'biodiversity index' were significantly higher in restored open‐canopy ponds than in unmanaged terrestrialized ponds. The three dytiscid water beetle species recorded in a tank were found to produce distinctive and recognizable sounds, indicating potential to create an audio reference library that could be used for automatic acoustic monitoring of freshwater arthropods. Pond soundscapes are rich in biological information and this study suggests that, with further development, automated passive ecoacoustic monitoring could be an effective non‐invasive technique for assessing pond conservation value and pond restoration and management success.